2020
DOI: 10.1001/jamanetworkopen.2020.0149
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bolus Feeding With Splanchnic and Cerebral Oxygen Utilization Efficiency Among Premature Infants With Anemia and After Blood Transfusion

Abstract: IMPORTANCE The pathogenesis of transfusion-associated necrotizing enterocolitis remains elusive. Splanchnic hypoperfusion associated with packed red blood cell transfusion (PRBCT) and feeding has been implicated, but studies of splanchnic tissue oxygenation with respect to feeding plus PRBCT are lacking. OBJECTIVE To investigate the oxygen utilization efficiency of preterm gut and brain challenged with bolus feeding during anemia and after transfusion using near-infrared spectroscopy. DESIGN, SETTING, AND PART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Feeding during transfusions may promote GI tract vulnerability by increasing the risk of tissue hypoxia,41,50 hypoperfusion, and anemia-related mucosal inflammation 43. A recent prospective cohort study of 25 VLBW infants receiving at least 120 mL/kg/d of feeds found insufficient postprandial mesenteric oxygen utilization for 8 hours following a transfusion 51…”
Section: Resultsmentioning
confidence: 99%
“…Feeding during transfusions may promote GI tract vulnerability by increasing the risk of tissue hypoxia,41,50 hypoperfusion, and anemia-related mucosal inflammation 43. A recent prospective cohort study of 25 VLBW infants receiving at least 120 mL/kg/d of feeds found insufficient postprandial mesenteric oxygen utilization for 8 hours following a transfusion 51…”
Section: Resultsmentioning
confidence: 99%
“…The physiologic buffer to secure cerebral oxygenation, with the trade-off of continued splanchnic tissue hypoxia in the immediate post-transfusion period may be a factor in the pathogenesis of TANEC. Splanchnic susceptibility may be further exacerbated by other factors, including storage RBC lesion that prevents effective oxygen offloading [ 41 ] and the negative effect of continued feeding during and immediately after PRBCT [ 23 , 42 45 ]. The median (IQR) age of transfused packed red blood cells was 13 (4–24) days.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology was similar, and many of the participants were included in the previously published study [ 23 ]. This prospective observational study was conducted in the neonatal intensive care at Nepean Hospital, Australia, (Sep 2014- Nov 2016)—Eligible participants included: gestation <32 weeks; birth weight <1500 grams (g); postmenstrual age <37 weeks; tolerating enteral feed volume ≥120 millilitres/kilogram/day (mL/Kg/day); hemodynamically stable and receiving elective PRBCT to treat anemia of prematurity.…”
Section: Methodsmentioning
confidence: 99%
“…The primary study evaluated cerebral and splanchnic oxygenation associated with PRBCT and feeding. 25 The study protocol including parental consent was approved by the human research ethics committee, Nepean Blue Mountain Local Health Committee (Approval number: Study 12/67 - HREC/12/NEPEAN/148). The study was conducted after written, informed consent of parents, as approved by the human research ethics committee, Nepean Blue Mountain Local Health Committee.…”
Section: Methodsmentioning
confidence: 99%